النزاعات المائية في حوض النيل وتداعياتها على الأمن المائي في شمال إفريقيا النزاع المصري الإثيوبي (أنموذجا). - البار امين; دني ايمان (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
يعد موضوع الأمن المائي اليوم من القضايا الحيوية والمحورية التي تهتم بها كل مراكز البحث والدراسات ، كما تسترعي اهتمام جاداَ وفائقاَ من طرف الباحثين ، و تحضى بأولوية كبيرة في أجندات الدول ، لما لهذا المورد من أهمية كبرى في حياة الأفراد والمجتمعات ، وتداعيات نذرته أو قلته على تحقيق الأمن المائي ، وحاجة الأفراد الماسة لهذا المورد وعلاقته المباشرة بتحقيق الأمن الغذائي ، والذي كان على مر العصور ومنذ بداية الإنسانية المطلب والحاجة الأولى للإنسان. وبهدف تحقيق الاكتفاء من هذا المورد وتحقيق الأمن المائي سعت الدول جاهدت إلى السيطرة على الموارد المائية المتاحة لها ، مما أدى إلى الكثير من النزاعات المائية ، والتي تقارب أحيانا أن تقودنا إلى حروب مائية ، وعلى سبيل مثال هذه النزاعات نجد: النزاع حول حوض الأردن ، حول نهري دجلة والفرات ، حول نهر النيل ، والنزاع حول سدُ النهضة الذي يشكل خطرا كبيرا على الأمن المائي والغذائي لكل من مصر والسودان ، وهذا ما سنتطرق إليه من خلال هذه الدراسة. Today, the issue of water security is one of the vital and pivotal issues that all research and studies centers are concerned with, and it also attracts serious and superior attention on the part of researchers, and is given a great priority in the agendas of countries, because of this resource of great importance in the lives of individuals and societies, and the repercussions of its vow or reduction on the lives of individuals and societies. Achieving water security, the urgent need of individuals for this resource and its direct relationship to achieving food security, which has been throughout the ages and since the beginning of humanity the first demand and need of man. With the aim of achieving sufficiency from this resource and achieving water security, countries have striven to control the water resources available to them, which has led to many water disputes, which sometimes come close to leading us to water wars. As an example of these disputes , we find : the dispute over the Jordan basin , over the Tigris and Euphrates rivers , over the the Nile river , and the dispute over the Renaissance Dam , which poses great threat to the water and food security in Egypt and Sudan , and this is what we will address thriugh this study.